Value based System Architecting: Illustrated by Designing a Task Automation System. Issue 1 (13th September 2016) - Kumar, Anand; Lokku, Doji Samson; Zope, Nikhil; Natarajan, Swaminathan
Abstract: Architecture is both a design activity (process) as well as the schema of fundamental things about a system (work product). As a design activity, architecture is the act of creating a representation of an unknown and original object whose properties (like technical aspects, formal and spatial structures) must be well enough understood in advance. As a work product, architecture is the structure of the components of a system, their interrelationships, externally visible properties of those components and principles and guidelines governing their design and evolution over time. In this paper, a systems architecting approach that is based on value viewpoint is discussed. This approach is illustrated for a task automation system.